Resilient Antarctic monsoonal climate prevented ice growth during the Eocene - Baatsen, Michiel; Bijl, Peter; Heydt, Anna; Sluijs, Appy; Dijkstra, Henk (2023)
Understanding the extreme greenhouse of the Eocene (56–34Ma ago) is key to anticipate potential future conditions. During the Eocene, the Antarctic continent remained mostly ice-free despite large temperature swings. Seemingly contradictory indications of ice and thriving vegetation complicate modelling efforts to explain the Antarctic Eocene climate. We use global climate model simulations to show that extreme seasonality mostly limited ice growth. Without ice sheets, much of the Antarctic continent saw monsoonal conditions. Perennially mild and wet conditions along Antarctic coastlines support vegetation reconstructions, while extreme seasonality elsewhere promoted intense weathering shown in proxy records. The results can thus explain the coexistence of warm and wet conditions in some regions, while small ice caps could form near the coast. The resilience of the climate regimes seen in these simulations agrees with the longevity of warm Antarctic conditions during the Eocene, but also challenge our view on glacial inception.